An overview of stakeholder awareness on forest and wood products certification initiative: students' perspective - Walter Lintangah; Nur Athirah Omardin (Zes Rokman Resources, 2015)
A study on the awareness of forest and wood products certification initiatives and its development was conducted among students taking courses related to forestry, environment and conservation biology in the Faculty of Sciences and Natural Resources at Universiti Malaysia Sabah. Questionnaires were distributed to a total of 437 respondents from first to third-year students. The results indicated that many students were more aware of the forest certification than wood products certification program. There were significant differences in the level of awareness of the students from different programs and their number of years of study. The first year students mainly knew the subject from the websites whereas second and third year students obtained the information from their lecturers. Most of the respondents agreed the importance of forest and wood products certification towards the achievement of sustainable forest management and biodiversity conservation, sustaining forest ecosystem services, and mitigating illegal logging activities. Nevertheless, many of those involved in the purchasing of paper did not know or consider forest and wood product certification logo as the factor that influenced them to buy the product. They agreed that there was a need to enhance campaigns pertaining to certification initiatives. The findings have implications for the government, NGOs, educational institutions, mass media and the parties directly responsible for forest management such as the Forestry Department and private sectors, suggesting that the development of forest certification initiatives can be strengthened through education, awareness programs, training courses, and the provision of funding.